KODIFIKASI PENGETAHUAN DAKWAH DIGITAL DI KANAL YOUTUBE MASJID RAYA SYEKH AHMAD KHATIB AL-MINANGKABAWI - Doni, Sefri; Rahmadi, Rahmadi (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2026)
Digital transformation has encouraged mosques to utilize YouTube as a medium of da’wah, yet the content produced is often not managed as a knowledge asset. This study aims to map the distribution and Islamic education function of the digital da’wah content of Masjid Raya Syekh Ahmad Khatib Al Minangkabawi, West Sumatra, to analyze the manifestation of knowledge conversion in the SECI model along with its codification compliance, and to formulate a knowledge management model. It employs a qualitative descriptive approach with content analysis of a census of 392 videos collected through the YouTube Data API v3. The findings reveal that the channel is dominated by a structured ta’lim function (65%), with a strong externalization stage (92% of content is themed) but an almost failing combination stage (0% tags, 2% descriptions) and an inconsistent naming taxonomy. From this pattern, a SECI-based Islamic education knowledge management model is formulated, positioning the combination stage as the leverage point for improvement. The study concludes that content productivity does not automatically correspond to the quality of knowledge management, and the proposed model offers a concrete and transferable direction for improvement for other mosques managing digital da’wah channels.